Cardiac morphology of North Island brown kiwi (Apteryx mantelli). Issue 3 (4th May 2023) - Khude, R; Huxley, J; Hunter, S; Wightman, P; Gartrell, BD
ABSTRACT: Aims: To investigate the cardiac anatomy of North Island brown kiwi ( Apteryx mantelli ) through heart morphometric parameters measured at post-mortem examination. Methods: Morphometric cardiac parameters were established at post-mortem examination of 20 North Island brown kiwi. Birds were classified by gender and age (chicks vs. adults). Measurements included: body mass, heart mass, sternal length, midpoint thickness of left ventricular free wall, midpoint thickness of right ventricular free wall and ratios of heart mass to body mass, left ventricular length to sternal length, right ventricular length to sternal length, length of left ventricle to right ventricle, interventricular septal thickness relative to the sternal length and interventricular septal thickness relative to the left ventricular length. Unadjusted estimates of the median difference and their 95% CI were then reported at each age and sex for all the cardiac morphometric parameters and their ratios. Results: The small sample size led to wide 95% CI for the median difference between gender and age for the cardiac morphometric measurements. Nevertheless, between adult female and male kiwi, the estimated population median differences for heart mass (2.2 (95% CI = −2.9–5.6) g), length (1.2 (95% CI = −2.2–5.6) mm), width (6.1 (95% CI = −1.0–8.2) mm), left ventricular free wall length (5.5 (95% CI = −0.5–8.8) mm) and right ventricular free wall length (2.6 (95% CI = −3.7–6.9) mm) were established. In adult North Island brown kiwi, the heart mass is 0.8 (95% CI = 0.7–0.8)% of the body mass. Conclusions: The precision of the differences noted in heart measurements recorded between male and female kiwi at each age was limited by the low sample size available for this study. This led to wide CI and an inability to adjust differences observed for gender by differences in other confounders such as body size. With this caveat, there is weak evidence that adult female kiwi have a larger heart size and mass than the adult males. Clinical relevance: These results can be used to improve the diagnosis of cardiac disease in kiwi at post-mortem examination and aid in interpretation of the results of echocardiography in live birds for the antemortem diagnosis of cardiac disorders.